Widening Horizons: The Story of Interserve - Makower,Katharine (London Hodder & Stoughton, 1993)
The history of Interserve, from its centenary in 1952 to the present day, is presented in a celebration of the work of this long-standing missionary society, looking at its increasing emphasis on co-operative ventures.
Keywords: Interserve -- History. Bible and Medical Missionary Fellowship -- History. Missions -- History